Konsep Zikir Sufistik dalam Tafsir Al-Qur’ān Al-Karīm Karya Mullā Ṣadrā - Ar-Ridho, Ahmed Zaranggi; Malia Hayati , Safira (Journal of Sufism and Psychotherapy, 2022)
Interpretation in Sufistic studies is often done partially by using only a practical Sufism approach so that it does not produce a comprehensive understanding of the concept of remembrance. Mulla adrā's interpretation has an interesting study, namely the theoretical and practical philosophical style so that it is able to read verses about the concept of remembrance comprehensively. Mullā adrā in the interpretation of Al-Qur'ān Al-Karīm offers the concept of Sufistic remembrance that considers aspects of theoretical Sufism with wujūdī hermeneutics. Hermeneutics offers a comprehensive reading involving three important components, namely textual, intellectual and spiritual. So as to produce a holistic interpretation of remembrance in the Qur'an. Therefore, this article aims to reveal the meaning of the concept of remembrance from adrā's perspective more comprehensively. To achieve this goal, this article uses a descriptive-analytical method. This article shows three important concepts in adrā's perspective of Sufistic remembrance. First, Sufistic remembrance must involve both outer and inner remembrance. Second, there are six levels of Sufistic remembrance which include ikr lisān, ikr jawārih wal arkān, ikr nafs, ikr qalb, ikr rūh and ikr sirr which are based on gradations of existence (tasykīk al-wujūd). Third, there are three states of a true remembrance (ahwāl aż-żākir al-haqīqī) based on the theory of the unity between the knower and the known (Ittiḥād al-āqil wa al-ma'qūl). These three key concepts illustrate the integrity of zikr in the interpretation of adrā which combines practical Sufism and theoretical Sufism.